Patched-1 and smoothened, a hedgehog receptor and signal transducer are highly expressed in diffuse large B-cell lymphoma - Azman, Siti Nur Lina; Hussin, Huzlinda; Md Said, Salmiah; Alias, Zanariah; Abdullah, Maizaton Atmadini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: The Hedgehog (Hh) signalling pathway is a developmental signalling pathway involved in normal mammalian developmental and homeostasis of adult renewable tissues. In most adult tissues, this pathway remains silent and previous studies have shown that constitutive activation of Hedgehog signalling pathway leads to various types of malignancies including medulloblastomas, basal cell carcinoma, gastrointestinal, breast and prostate cancer. The purpose of this study was to investigate the immunohistochemical expression of Hedgehog pathway proteins in Diffuse Large B-cell Lymphoma and determine their association with overall survival (OS). Methods: Positive control using normal tonsils were included in each batch of immunohistochemical staining procedure. Results: PTCH1 proteins were highly expressed in DLBCL and showed strong staining intensity in 107 (100%) cases and SMO proteins were expressed in 105 (98.1%) cases. PTCH1 proteins were localised in the nucleus of tumour cells, whereas SMO proteins were mainly localised in the cytoplasm of tumour cells. Positive expression of PTCH1 and SMO proteins and overall survival of DLBCL patients were correlated with age, gender, race and tumour location. There was no significant correlation between the expression of these two proteins with any of the parameters. PTCH1 expression showed significant association with SMO expression (P=0.03). Conclusions: Our findings suggest that high expression of both PTCH1 and SMO may be important in the pathogenesis of DLBCL. However, additional mechanisms that may contribute to the activation of HH signalling in DLBCL needs to be further explored.